Comparação de massagem, estimulação elétrica transcutânea e placebo para alívio da dor durante o trabalho de parto: ensaio clínico randomizado - Dias, Naiara Toledo (2022)
Introduction: The intensity of pain during labor can impair a woman's experience and satisfaction with childbirth. In view of this, investigations regarding the effects of non-pharmacological pain relief methods during labor gain importance. Objectives: To verify the effects of massage, transcutaneous electrical stimulation (TENS) and placebo, in addition to usual care, on pain, satisfaction with childbirth, childbirth outcomes and birth conditions of the newborn. Material and methods: This are a randomized controlled clinical trial with a non-probabilistic convenience sample, composed of women in the first active stage of childbirth, hospitalized in a public institution. The participants were divided into three groups that received continuous support from professionals, encouragement to walk and to adopt vertical postures. In addition, the parturients in the Massage group (n=36) received massage in the lumbosacral region for 30 min, the participants in the TENS Group (n=36) received the application of TENS for 30 min and the participants in the Placebo Group (n=36 ) received the application of placebo TENS for 30 min. The primary endpoint assessed was the change in the Visual Analogue Scale (VAS) from baseline to immediately after the intervention. Secondary outcomes include change in VAS from baseline to 30 minutes and 1 hour after the intervention, and in the immediate postpartum period (12-24 hours after labor). Participants' satisfaction with childbirth were also evaluated through the Questionnaire of Experience and Satisfaction with Childbirth (QESP) and variables related to childbirth and the newborn's birth conditions collected from the medical record. Results: Immediately after the intervention, the TENS group showed a reduction in reported pain, while the Placebo group showed an increase in pain (p<0.001). No significant differences were observed between groups 30 minutes and 1 hour after the intervention or after delivery. The QESP results showed differences only in the support subscale, being higher in the Massage group. Data regarding delivery and newborn outcomes were similar between groups. Conclusion: Therefore, the use of TENS associated with other non-pharmacological methods of pain relief in the first stage of labor leads to a reduction in pain, does not interfere with delivery outcomes and is safe for the neonate, proving to be superior to the other methods evaluated.